Breath Meditation and Emotional Regulation: Psychosomatic and Neural Mechanisms in a 21-Day Study - Cieśla, Piotr; Cieśla, Magdalena; Bernatek, Małgorzata (Człowiek i Społeczeństwo, 2026)
This study investigates the effects of a 21-day breath meditation intervention on emotional well-being, with a focus on the psychosomatic and neural mechanisms of breath regulation. Breath meditation, known to activate the parasympathetic nervous system and reduce physiological markers of stress, has been shown to enhance emotional regulation and improve subjective well-being. The study included 112 adult participants, divided into four groups, each engaging in different combinations of breath meditation, body scanning, and positive reflection exercises. Emotional well-being was assessed using the SUPIN (Polish adaptation of the PANAS), measuring positive and negative affect pre- and post-intervention. Results indicate significant improvements in positive affect and reductions in negative affect for groups practicing breath meditation, especially when combined with positive reflection. Group 2 (Breath Meditation + “Three Good Things”) showed the largest increases in positive affect and reductions in negative affect, highlighting the synergistic effect of combining mindfulness with positive psychology exercises. These findings underscore the efficacy of breath meditation as a brief, non-invasive intervention for emotional well-being and stress regulation. The study offers insights into practical applications for mental health, educational, and workplace settings, emphasizing the potential of breath-focused mindfulness practices to foster resilience and emotional balance. Future research should explore long-term effects and physiological markers to deepen understanding of these interventions’ mechanisms and sustainability.